Whey protein hydrolysate alleviated acetaminophen-induced hepatocyte pyroptosis by activating mitophagy - S. Zhang; J. Guo; M. Liu; Y. Chen; X. Shen; J. Wang; X. Deng; S. Guan (Journal of Dairy Science)
ABSTRACT: Whey protein is widely recognized as a high-quality protein source, primarily derived from dairy products. This type of protein is valued not only for its remarkable nutritional benefits but also for its substantial antioxidant properties and its capacity to reduce inflammation. Previous studies have demonstrated that whey protein hydrolysate (WPH) is effective in both the prevention and treatment of liver injury caused by acetaminophen (APAP) overdose. Pyroptosis is a form of programmed cell death that significantly contributes to liver damage induced by APAP, and it is associated with increased levels of oxidative stress and inflammation. However, the specific mechanisms by which WPH influences pyroptosis remain not fully understood. The present study observed a significant alleviation of APAP-induced hepatocyte injury by WPH, alongside a reduction in the release of proinflammatory factors, specifically IL-1β and -18. Moreover, the expression levels of pyroptosis-related proteins, including NLRP3, GSDMD-N (N terminal fragment), and cleaved CASP1, were significantly reduced following treatment with WPH. In the subsequent phase of our research, we examined the levels of reactive oxygen species (ROS) and the expression of CTSB in hepatocytes. Increased levels of ROS resulted in heightened permeability of lysosomal membranes, which led to the release of CTSB into the cytosol. The liberated CTSB subsequently activated the NLRP3 inflammasome, thereby promoting pyroptosis. Our results revealed that WPH reduced the accumulation of ROS in hepatocytes and inhibited the release of CTSB. In subsequent mechanistic studies, we found that WPH upregulated the expression of PRKN, PINK1, and microtubule-associated protein 1 LC3, while downregulating the expression of P62 to activate mitophagy. We further validated these results by introducing the mitophagy inhibitor cyclosporin A. In conclusion, our findings suggest that WPH may enhance the removal of damaged mitochondria through the activation of the mitophagy mechanism. This process may lead to a reduction in intracellular ROS accumulation and mitigate APAP-induced activation of the NLRP3 inflammasome and pyroptosis.